2010
DOI: 10.11157/anzswj-vol22iss2id197
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner research made easier: A report on the GRIP project

Abstract: An article in this journal in 2007 outlined an innovative programme in progress in Auckland at that time. Growing Research in Practice (GRIP) involved groups of social service practitioners who carried out small and manageable research projects on topics that piqued their interest within the workplace. The main aim of the GRIP programme was to nurture a culture of practitioner enquiry in social service agencies in Auckland, in an attempt at facilitating meaningful change and service improvement in the longer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In general, social workers in practice struggle to find the time and confidence to engage with research (Beddoe et al 2010;Pain 2011;Goel et al 2018), with a value conflict inherent in organisational culture surrounding research in practice (Shannon 2013). This is particularly true for hospital-based social workers, immersed in a quantitative research culture, dominated by medical and nursing colleagues and driven by evidence-based methodologies (Beddoe et al 2007).…”
Section: My Identity As a Social Work Researchermentioning
confidence: 99%
“…In general, social workers in practice struggle to find the time and confidence to engage with research (Beddoe et al 2010;Pain 2011;Goel et al 2018), with a value conflict inherent in organisational culture surrounding research in practice (Shannon 2013). This is particularly true for hospital-based social workers, immersed in a quantitative research culture, dominated by medical and nursing colleagues and driven by evidence-based methodologies (Beddoe et al 2007).…”
Section: My Identity As a Social Work Researchermentioning
confidence: 99%
“…The dominance of the medical model in a hospital setting can challenge the social workers’ professional identity and claims to validity (Beddoe, 2013), highlighted in the shared research space where social work is partnering with other disciplines on research projects (Joubert, 2006). The prevalence of evidence-based practice in the health context has largely left social work practitioners asserting that forms of knowledge that align with social work ways of being, or ways of communicating, and engaging with vulnerable peoples are relegated or deemed invalid (Beddoe et al, 2010). This can include the absence of recognition of data or methodologies that emphasise consumer voices and context-driven experiences (Beddoe et al, 2007), creating a clash of values for those social workers wanting to research (Shannon, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ocial workers must understand their responsibility for research and publications (ANZASW, 2013;SWRB 2016), develop "research-mindedness" (Flynn & McDermott, 2016), including being ongoing critical consumers of research evidence that can be incorporated into everyday practice (Gray, Plath, & Webb, 2009), and increasingly, become social work research practitioners (Beddoe, Yates, Fouche, & Harington, 2010). As a social work educator who works alongside students to understand the value of research evidence in decision-making, I found this text helpful and highly recommend it as a resource for students and graduates.…”
mentioning
confidence: 99%